2017
DOI: 10.2903/sp.efsa.2017.en-1285
|View full text |Cite
|
Sign up to set email alerts
|

Data analysis and predictive modelling of HPAI H5 and H7 outbreaks in the EU 2005‐2015

Abstract: All data from reported HPAI outbreaks in the period 2005 -2015 were collected and analysed with respect to its value for quantifying transmission of HPAI to other flocks, preferably in the form of a transmission kernel. The strain type, farm type and host species was taken into account. In total 345 outbreaks were registered. To quantify transmission to other flocks, the traced contacts are relevant. Even more interesting than the traced contacts, is the transmission to neighbouring farms, since it helps in qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…We found a large variation in the estimated R 0 , latency and infectiousness between the studies, supporting a previous study of estimates restricted to experimental data (Central Veterinary Institute et al., 2017 ). These parameters are crucial when planning the response to an outbreak, especially if the response is based on simulation studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found a large variation in the estimated R 0 , latency and infectiousness between the studies, supporting a previous study of estimates restricted to experimental data (Central Veterinary Institute et al., 2017 ). These parameters are crucial when planning the response to an outbreak, especially if the response is based on simulation studies.…”
Section: Discussionsupporting
confidence: 89%
“…( 2021 ) found differences in the infectiousness of AIV between turkeys and chickens, with viremia higher in turkeys than in chickens in the case of LPAI. In contrast, a previous review of experimental data found that the range of R 0 for chickens, turkeys and ducks overlapped considerably, indicating that there might be no real difference (Central Veterinary Institute et al., 2017 ). The different R 0 estimates between species should be utilized when designing the response to outbreaks: biosecurity could be focused on high risk species such as ducks and turkeys, while chickens and poultry in general might exhibit a reduced risk of transmission.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Because the flock was culled on 6 December, the number of dead ducks observed on the morning of that day (300) did not represent a full day's mortality and, hence, was not used for fitting the model. As shown in Table 1, the transmission rate and the mean durations of the latent and infectious periods were assigned informative gamma priors, calibrated from the literature (Hobbelen et al., 2020 ; Koeijer et al., 2017 ). In the absence of relevant information, the shape parameters of the latent and infectious periods were given uniform distributions between 0 and 5 and between 0 and 20, respectively.…”
Section: Methodsmentioning
confidence: 99%